A Strategy for Constructing Pore‐Space‐Partitioned MOFs with High Uptake Capacity for C2 Hydrocarbons and CO2. (26th August 2020) - Wang, Yong; Jia, Xiaoxia; Yang, Huajun; Wang, Yanxiang; Chen, Xitong; Hong, Anh N.; Li, Jinping; Bu, Xianhui; Feng, Pingyun
Abstract: Introduction of pore partition agents into hexagonal channels of MIL‐88 type (acs topology) endows materials with high tunability in gas sorption. Here, we report a strategy to partition acs framework into pacs (partitioned acs) crystalline porous materials (CPM). This strategy is based on insertion of in situ synthesized 4, 4′‐dipyridylsulfide (dps) ligands. One third of open metal sites in the acs net are retained in pacs MOFs; two thirds are used for pore‐space partition. The Co2 V‐pacs MOFs exhibit near or at record high uptake capacities for C2 H2, C2 H4, C2 H6, and CO2 among MOFs. The storage capacity of C2 H2 is 234 cm 3  g −1 (298 K) and 330 cm 3  g −1 (273 K) at 1 atm for CPM‐733‐dps (the Co2 V‐BDC form, BDC=1, 4‐benzenedicarboxylate). These high uptake capacities are accomplished with low heat of adsorption, a feature desirable for low‐energy‐cost adsorbent regeneration. CPM‐733‐dps is stable and shows no loss of C2 H2 adsorption capacity following multiple adsorption–desorption cycles. Abstract : Record‐setting amounts of small hydrocarbon gas molecules such as acetylene and ethylene can be captured in a bimetallic cobalt–vanadium material synthesized by an unusual form of pore‐space partition.